Reconciliation as Public Theology: Christian Thought in Comparative Indigenous Politics - O’Sullivan, Dominic (International Journal of Public Theology, 2014)
Abstract Christian public theology extends reconciliation beyond its principal sacramental concern for relationships between God and penitent to the construction of ‘socially just’ public relationships for the settlement of intra-national conflict. In theological terms, reconciliation brings public relationships into what Hally calls ‘the Christ narrative of passion, death and resurrection’ in which the perpetrators of injustice repent and seek forgiveness. This article introduces the conflicts that these discourses aim to resolve in Australia, Fiji and New Zealand and explains and contrasts reconciliation’s relative importance in each of these jurisdictions. Moreover, the article’s cross-jurisdictional comparison shows reconciliation’s limits and possibilities as public theology, and argues that in Australia and New Zealand it has helped to create political environments willing to admit indigenous perspectives on a range of policy issues. On the contrary, however, the article also shows that the Fijian churches have distorted the concept of reconciliation to support political imperatives that are difficult to rationalize theologically, even though they are presented by the churches as being concerned with religious goals.
Keywords: christianity; colonisation; kāwanatanga; reconciliation; religion

Reconciliation: The Political Theological Nexus in Australasian Indigenous Public Policy - O’Sullivan, Dominic (International Journal of Public Theology, 2010)
Reconciliation brings together Christological and anthropological dimensions of human thought to illustrate the nexus between religious principles and political means. For the state reconciliation is concerned with social cohesion and political stability. For the church, it extends the sacramental notion of reconciliation between God and penitent to public relationships. This article examines Roman Catholic contributions to secular reconciliation debates. It shows how religious precepts create moral imperatives to engagement with secular discourses as a necessary element of Christian mission. It also argues that the church’s role in the disruption of indigenous societies creates an additional moral imperative to engage in reconciliation as mission and to articulate a Christian vision of indigenous rights.
Keywords: christianity; kāwanatanga; open access version available; reconciliation; tiriti o waitangi/treaty of waitangi; treaty obligations; treaty settlements